Effect of Blending Methods on the Mechanical Properties of PALF-Cotton Hybrid Yarns Produced via Open-End Spinning - Rusman, Fahmi Fawzy; Afifuddin, Mokh; Harianto, Dedy; Parmawati, Sih; Kusnadi, Bambang; Ardiyanto, Agus; Hindardi, Darmawan (TECHNO: JURNAL PENELITIAN, 2025)
The increasing demand for eco-friendly materials in the textile industry has led to greater attention on the use of natural fibers, such as pineapple leaf fiber (PALF), which is abundant as agricultural waste. However, its coarse structure and limited spinnability pose challenges in yarn manufacturing. This study aims to compare two fiber blending methods, sliver blending using a drawing frame and fiber blending using a blowing machine in the production of PALF-cotton hybrid yarns via an open-end spinning system. Both samples were prepared using a 50:50 PALF-cotton ratio and evaluated for yarn count, tenacity, and elongation. The results showed that the yarns blended through the blowing process demonstrated superior tenacity and more consistent yarn count. Statistical analysis using an independent sample t-test confirmed that these differences were significant (p 0.05). Elongation values were also significantly higher in yarns processed using the blowing method. These findings highlight the importance of blending technique in improving fiber distribution, inter fiber cohesion, and overall yarn quality. It can be concluded that the blowing method offers a more effective strategy for producing sustainable PALF-cotton hybrid yarns, suitable for industrial scale applications. This research contributes to the advancement of sustainable textile processing and provides a practical reference for industries seeking to utilize agro waste fibers in yarn production.